2015
DOI: 10.4103/0974-9233.167821
|View full text |Cite
|
Sign up to set email alerts
|

One year outcomes of photorefractive keratectomy with the application of mitomycin-C in the treatment of mild to moderate hyperopia

Abstract: Purpose:To evaluate refractive and visual outcomes of photorefractive keratectomy with mitomycin-C. (PRK-MMC) for the treatment of mild to moderate hyperopia.Materials and Methods:This case series enrolled 21 patients with up to +5.50 diopters (D) of hyperopia. All 42 eyes were treated with the Concerto (Wavelight) or the Technolas 217-Z (Bausch and Lomb) excimer laser. Outcome measures included best corrected distance vision acuity (BCVA) and uncorrected distance vision correction and refraction at 1, 3, 6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies have shown the safety and efficacy of different types of refractive surgeries such as LASIK and PRK in the correction of myopia or hyperopia with low to moderate astigmatism. 8 , 9 , 10 Katz et al. 11 have compared the 6-month results of LASIK and PRK for the correction of astigmatism greater than 3.0 D and concluded that both procedures have similar safety (1.01 ± 0.17 vs. 1.10 ± 0.26), efficacy (0.74 ± 0.19 vs. 0.76 ± 0.32), and predictability (67% vs. 65% within ±0.5 D), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the safety and efficacy of different types of refractive surgeries such as LASIK and PRK in the correction of myopia or hyperopia with low to moderate astigmatism. 8 , 9 , 10 Katz et al. 11 have compared the 6-month results of LASIK and PRK for the correction of astigmatism greater than 3.0 D and concluded that both procedures have similar safety (1.01 ± 0.17 vs. 1.10 ± 0.26), efficacy (0.74 ± 0.19 vs. 0.76 ± 0.32), and predictability (67% vs. 65% within ±0.5 D), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MMC in PRK has helped minimize postoperative haze, and the haze reported in our study is similar to what has been reported by other authors using MMC with alcohol, mechanical, and transepithelial PRK. 8,9,23,35,36 In addition, it was significantly better than the haze reported in earlier studies in which PRK was performed without the use of MMC, resulting in up to 40% of eyes developing haze, including the development of Salzmann nodular degeneration in some eyes. 5 In addition, the application of SmartPulse technology, and other excimer algorithms designed to optimize the ablated surface, is expected to lead to the development of less haze in the periphery of the stromal bed in PRK-treated hyperopic eyes.…”
Section: Discussionmentioning
confidence: 83%